Religious humanism in language education for sport students - Perdana, Satya (Journal Humanitarian Responsibilities, Education & Sport Sciences (JHRESS), 2021)
Education as an implementation of improving the quality of life must lead to the welfare of human life. The manifestation of the purpose of life, planting, internalization, and transforming educational values are expected to advance civilization. In the current era of globalization, the importance of the development of education is increasing. The philosophy of education is the key in the implementation of education in the main direction of benefiting all humans. Using systematic review, this study examines, examines, evaluates, classifies, and categorizes evidence that has been done previously. The philosophy of religious humanism education in the language of sports students is the true educational philosophy to encourage and motivate the language skills of sports students (physical education, coaching education, and sports science). This is manifested by human values or the process of humanizing humans in their essence as creatures of the Almighty God. In the educational process, the educational theory of humanism philosophy tends to guide sport students to be able to think, prioritize experience, and be actively involved in the language learning process. The communicative and functional linguistic competence of sports students as human beings must be based on efforts to humanize humans themselves so that the potential for their linguistic skills can be strengthened or increased.